Ways to enhance the efficiency of tuberculosis prevention in the children exposed to tuberculous infection illustrated by the example of Perm Kray - N. A. Bаrminа; L. A. Bаryshnikovа (Туберкулез и болезни лёгких)
The objective of the study: to characterize nidi of tuberculous infection of category I where children are living and effectiveness of tuberculosis prevention activities for the children living there.Subjects and methods. The degree of the risk of the epidemic breakout was assessed in the nidi of tuberculous infection where 520 children were living, results of skin tests were studied in 122 children from those nidi exposed to tuberculosis patients with no bacillary excretion, 263 children exposed to infectious patients, 112 children exposed to multiple drug resistant tuberculosis. The group of children (42 persons) from tuberculous infection nidi who developed active tuberculosis was also studied.Results of the study. It was found out that in two third of the nidi, where children were living, TB patients were excreting tuberculous bacilli, and in more than half of cases the source of infection was drug resistant, of which the majority of nidi (68.4%) had MDR MTB and 12.6% – extensive drug resistance. Each fifth case (21.5%) had concurrent HIV infection. In the nidus with a lethal case, 4.6% of children were contacting a case with TB/HIV co-infection and MDR/XDR. The mean age of the children who developed tuberculosis after exposure to the infection made 5.27± 3.17 years old, and 90.5% of cases were children exposed to a tuberculosis case with bacillary excretion, of 36.8% was exposed to an MDR TB case and 10.5% – to XDR TB. The hyperergic result of the test with TRA was confidently more frequent in all the groups versus Mantoux test (p < 0.05). It indicated of the heavy epidemic burden of the tuberculous infection nidus and proved the need to pay very close attention to this group of patients and their neighbors.In tuberculous infection nidi, where active tuberculosis was registered among children, the anti-tuberculosis activities were investigated and it was found out that their quality including preventive treatment was poor.